Analysis of internal restrictions and their impact on the competitiveness of MYPES in the textile apparel sector of the district of Tacna, period 2007-2008 - Pomareda Angulo, Elena (2012)
This is a basic research descriptive and correlational research work, because it is based on specifying properties, characteristics and relationshíp between variables studied, namely internal restrictions and competitiveness of MYPES in clothing manufacturing area. We included information collected through a questionnaire applied to 100 microbusinessmen in the small and micro enterprises in Tacna district in orden to determine the existing internal restrictions and their competitiveness. Our objective was to determine how it is that internal restrictions influence on competitiveness of MYPES in clothing manufacturing areas in the district of Tacna in the study period 2007-2008. The most important results are that internal restrictions that influence mainly on competitiveness in clothing manufacturing area are: limitation in managerial capacities, scarce operative capacities and low technology levels. This is evidenced on limited business capabilitics. Most CEOs are empiric, they don't develop managerial capabilities to solve existing problems, such as leading a working team,  deal with hard discipline situations and also deal with interests that appcar in group and also achievement of results. MYPES are characterized by their low level of competitiveness due to their low productivity since businessmen in charge have not made efficient use of their resources (supplies) when manufacturing their products.